MYRIAPORA SCIUTOI N. SP., A NEW FOSSIL ATLANTO-MEDITERRANEAN BRYOZOAN SPECIES, AND COMMENTS ON ALLIED TAXA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2015)
We describe a new fossil species of Myriapora, M. sciutoi n. sp., which is similar in general appearance to the Recent, Atlantic, deep-sea species M. bugei d'Hondt, 1975. The new species has been found in sediments of the late Tortonian-Messinian of NW Morocco, and the Gelasian of NE Sicily and south Calabria, Italy. The main diagnostic characters of the new species are: erect, rigid growth, with lateral branches developing at right angles; arrangement of the zooids in whorls; dimorphic orifice, which has a very marked sinus in autozooids; prominent ooecia usually present in all the zooids from the same whorl. The previous diagnosis of the genus has been amended in order to include the presence of species with zooids arranged in whorls, in addition to those arranged quincuncially. A generic reassignment to Myriapora or to the allied genus Leieschara for all the known species to date is also proposed. The geographical and stratigraphical distribution of M. sciutoi n. sp. suggests a recolonization of the Mediterranean, after the Messinian Salinity Crisis, from founder populations that have survived in the Atlantic.
Keywords: Taxonomy; Myriaporidae; Leieschara; deep-sea; Cenozoic; Tortonian; Messinian; Gelasian